Sepsis prevents the development of experimental type 1 diabetes - Stegnjaić, Goran; Mićanović, Dragica; Saksida, Tamara; Despotović, Sanja; Griffith, Thomas S.; Badovinac, Vladimir P.; Miljković, Đorđe; Stanisavljević, Suzana (Frontiers in Immunology, 2025)
IntroductionWhile both sepsis and autoimmunity are characterized by dysregulated immune responses, their mutual influence remains only partially understood.MethodsIn this study, we investigated how sepsis affects the development of type 1 diabetes (T1D), an autoimmune disease characterized by the destruction of pancreatic β-cells. Specifically, we examined the impact of polymicrobial sepsis on the progression of T1D induced by multiple low doses of streptozotocin (MLDS). C57BL/6 mice were subjected to cecal ligation and puncture (CLP) to induce sepsis, and T1D was subsequently induced using the MLDS protocol after the mice had fully recovered from the acute phase of sepsis.Results and discussionAlthough CLP triggered transient hypoglycemia, it did not impair the structure or function of the endocrine pancreas, and the mice were normoglycemic at the time of T1D induction. Notably, CLP limited immune cell infiltration into the pancreas following MLDS treatment, thereby preventing the onset of T1D and the development of hyperglycemia. CD4+ T cells are important for initiating the autoimmune attack on pancreatic islets by activating CD8+ T cells and macrophages. Thus, it seems plausible that the protective effect observed in CLP-exposed mice was due to the reduction in CD4+ T cells, but not CD8+ T cells, in the pancreatic lymph nodes. Additionally, CD4+ T cells and regulatory T cells in the spleens of CLP-treated mice exhibited elevated expression of inhibitory/exhaustion markers. These findings suggest that sepsis-induced alterations in the CD4+ T cell compartment within pancreas-associated lymphoid organs confer protection against MLDS-induced T1D.